Anti-protozoal activity of Thymol and a Thymol ester against Cryptosporidium parvum in cell culture. (April 2021) - Dominguez-Uscanga, Astrid; Aycart, Danielle Francesca; Li, Kun; Witola, William H.; Andrade Laborde, Juan E.
Abstract: Cryptosporidium parvum is a protozoan parasite that infects intestinal epithelial cells causing malabsorption and severe diarrhea. The monoterpene thymol has been reported to have antifungal and antibacterial properties but less is known about the antiparasitic effect of this compound. Terpenes are sometimes unsuitable for therapeutic and food applications because of their instability. Esterification of terpenes eliminates this disadvantage. The present study evaluates the effects of thymol (Th) and a thymol ester, thymol octanoate (TO), against C. parvum infectivity in vitro . The cytotoxicity IC50 value for TO after 24 h of treatment was 309.6 μg/mL, significantly higher than that of Th (122.5 μg/mL) in a human adenocarcinoma cell line (HCT-8). In the same way, following 48 h of treatment, the cytotoxicity IC50 value for TO was significantly higher (139 μg/mL) than that of Th (75.5 μg/mL). These results indicate that esterification significantly reduces Th cytotoxicity. Dose-dependent effects were observed for TO and Th when both parasite invasion and parasite growth assays were evaluated. When evaluated for their activity against C. parvum growth cultured in vitro in HCT-8 cells, the anti-cryptosporidial IC50 values were 35.5 and 7.5 μg/mL, for TO and Th, respectively. Together, these findings indicate that esterified thymol has anti-cryptosporidial effect comparable with its parental compound thymol, but with improved safety margins in mammalian cells and better physicochemical properties that could make it more suitable for diverse applications as an antiparasitic agent. Graphical abstract: Image 1 Highlights: Thymol and thymol octanoate were active against C. parvum in vitro, with low cytotoxicity in HCT-8 cells. Esterified thymol has anti-cryptosporidial effect comparable with its parental compound but with improved physicochemical properties. Thymol had a stronger effect than thymol octanoate against C. parvum invasion but similar effects when parasite growth was evaluated.